Language Curriculum Innovation in a Chinese Secondary School A Study of Teacher Cognition and Classroom Practices - Zhu, Yan (Springer Singapore, 2018)
This book offers a comprehensive overview of the changes in foreign language teachers' cognition and practices during a four-year innovation project at a Chinese secondary school, and explores the factors that influenced the trajectory of those changes. It makes a substantial contribution to research on educational change by offering a longitudinal observation of the facts and voices in EFL settings in China; as such, the book offers a valuable resource for scholars, teacher educators, teachers, and others interested in initiating, managing and evaluating innovations in EFL classrooms.